2001
DOI: 10.1107/s0907444901007284
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and crystallization of a novelSarcocystis murislectin, SML-2

Abstract: A novel lectin (SML-2) consisting of 138 amino acids was isolated from cyst merozoites of Sarcocystis muris and sequenced by Edman degradation and mass spectrometry. All 12 cysteinyl residues are involved in disul®de bridges, four of which are attributed to a characteristic pattern of cysteines as found in the so-called PANmodule superfamily. Crystals of SML-2 diffracting to 2.1 A Ê resolution at a synchrotron were grown by the hanging-drop vapour-diffusion technique. They belong to the space group P2 1 2 1 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…Refinement details for 5–7 : All non‐hydrogen atoms but the water molecule of crystallization (O2w) and the two uncoordinated oxygen atoms of the gangling nitrate ion (O5N and O6N), which are disordered, were refined anisotropically. The former was modeled over two sites (O2w and O2wa), basically 50:50 occupied (their relative occupancies were refined freely within SHELXL while constraining the sum of the occupancies to unity,55 reaching values of 0.54:0.46 ( 5 ), 0.56:0.44 ( 6 ), and 0.54:0.46 ( 7 ) at convergence). A good model for the disorder of the gangling nitrate ion could not be found.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Refinement details for 5–7 : All non‐hydrogen atoms but the water molecule of crystallization (O2w) and the two uncoordinated oxygen atoms of the gangling nitrate ion (O5N and O6N), which are disordered, were refined anisotropically. The former was modeled over two sites (O2w and O2wa), basically 50:50 occupied (their relative occupancies were refined freely within SHELXL while constraining the sum of the occupancies to unity,55 reaching values of 0.54:0.46 ( 5 ), 0.56:0.44 ( 6 ), and 0.54:0.46 ( 7 ) at convergence). A good model for the disorder of the gangling nitrate ion could not be found.…”
Section: Methodsmentioning
confidence: 99%
“…A good model for the disorder of the gangling nitrate ion could not be found. Instead, similarity restraints on 1–2 and 1–3 distances and displacement parameters as well as rigid bond restraints55, 56 for anisotropic displacement parameters were applied to both the two nitrate ions and the two acetonitrile solvent molecules in the structures of 5–7 .…”
Section: Methodsmentioning
confidence: 99%
“…Here, we present the high-resolution crystal structure of a galactose-specific S. muris lectin: the major micronemal protein SML-2 (Eschenbacher et al, 1993;Mü ller et al, 2001). A recent very low resolution ab initio structure determination of SML-2 provided some insight into the shape and symmetry of the homodimeric protein (Mü ller et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…A recent very low resolution ab initio structure determination of SML-2 provided some insight into the shape and symmetry of the homodimeric protein (Mü ller et al, 2006). In the absence of a suitable model for molecular-replacement phasing, the presence of six disulfide bridges, as identified by mass spectrometry (Mü ller et al, 2001), and five methionine residues per SML-2 molecule suggested the use of the sulfur phasing method for structure determination at 1.95 Å resolution. Furthermore, to analyze the structural basis of the specificity of the lectin towards galactose, complexes of SML-2 with 1-thio--d-galactose in space groups C222 1 and P2 1 2 1 2 1 were characterized.…”
Section: Introductionmentioning
confidence: 99%
“…However, complete sequencing of the two native lectins isolated from S. muris cyst merozoites gave an unexpected result. Whereas one sequence is in total agreement with the deduced aa sequence of the cDNA clone encoding mature SML1, the second did not match with the suggested sequences of the two clones mentioned above (Mueller et al 2001). This implies that the Sarcocystis genome harbours a third gene encoding a microneme protein (SML2) of cyst merozoites.…”
mentioning
confidence: 42%